2019
DOI: 10.1016/j.jssc.2018.12.037
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable crystal chemistry of the Ca14AlSb11 structure type, magnetic and thermoelectric properties

Abstract: Yb14MnSb11 is a member of a remarkable structural family of compounds that are classified according to the concept of Zintl. This structure type, of which the prototype is Ca14AlSb11, provides a flexible framework for tuning structure-property relationships and hence the physical and chemical properties of compounds. Compounds within this family show exceptional high temperature thermoelectric performance at temperatures above 300 K and unique magnetic and transport behavior at temperatures below 300 K. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 123 publications
(194 reference statements)
2
93
0
Order By: Relevance
“…S5). This increase in effective mass with temperature and carrier concentration is what previous experimental studies ( 4 , 25 ) have been reported for different compounds of the A 14 MPn 11 structure and is seen in Fig. 5B .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…S5). This increase in effective mass with temperature and carrier concentration is what previous experimental studies ( 4 , 25 ) have been reported for different compounds of the A 14 MPn 11 structure and is seen in Fig. 5B .…”
Section: Resultssupporting
confidence: 88%
“…However, this study could not explain why the Seebeck coefficient of differently doped samples appears to converge near room temperature instead of the expected 0 K for an SPB semiconductor with constant m * ( 24 ). Hu et al ( 4 ) and Kunz Wille et al ( 25 ) have shown the experimental DOS effective mass of A 14 M Pn 11 markedly increases with increasing temperature and suggested a deviation from SPB.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivity of 0.56 W m -1 K -1 at 300 K is comparable to that of state-of-the-art thermoelectric materials, such as Yb14MnSb11 (0.7 Wm -1 K -1 at 300 K), Bi0.5Sb1.5Te3 (~0.7 Wm -1 K -1 at 300 K), [010] direction of the SnSe single crystal (0.7 Wm -1 K -1 at 300 K), Zn8Sb7 (0.6 Wm -1 K -1 at 400 K), Ba8Cu14Ge6P26 (0.77 Wm -1 K -1 at 300 K), and LaxBa8-xCu16P30 (~1.1 Wm -1 K -1 at 400 K). [53][54][55][56][57][58] Ba2Si3P6 displays a relatively low absolute value of Seebeck coefficient (−30 µV/K at 300 K) and high resistivity (83 Ωm at 300 K) (Figure 3 middle and bottom). The negative nature of the Seebeck and temperature dependence of resistivity suggest Ba2Si3P6 to be a n-type semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] A notable example is the well-known Yb 14 MnSb 11 , which has been identified as an efficient high-temperature p-type leg for thermoelectric generators. [11][12][13] Examining the reported compounds in the ternary alkali metal-antimonide systems, two things become apparent: (i) there is a high number of compounds with 111 stoichiometry that crystallize in extraordinarily common ZrBeSi or PbFCl structure types; and (ii) that a large number of these compounds are found for the lighter alkali metals (Li, Na, or K) while the heavier metals (Rb or Cs) are underrepresented. [14][15] The latter point is not as easily explained.…”
Section: Introductionmentioning
confidence: 99%